Material Development Principles for EFL Students Teachers to Face Education 5.0: Integrating Diversity and Inclusivity - Fadhila Yonata (Fakultas Komunikasi, Sastra, dan Bahasa, 2024)
The material development course is one of the most important courses in the initial teacher education (ITE) program since student teachers have to understand how to develop EFL materials for their classroom needs. However, academic literature has limitedly discussed principles of material development courses to deal with contemporary global citizenship education and education 5.0 era. This article proposes a conceptual framework to encourage material development in EFL student teachers at the undergraduate level. The study starts with the justification of the gap between classrooms and contemporary society portraits. To fill this niche, this conceptual study draws on Widodo et al. (2022) regarding the framework for language material development and diversity in ELT proposed by Banegas et al. (2021) to offer a conceptual model for EFL teachers and material developers. Hopefully, the concept helps EFL practitioners design learning materials purposively accommodating diversity and inclusivity for foreseeable global citizens.